New dinor-cis-labdane diterpene and flavonoids with antimycobacterium activity from colebrookea oppositifolia - Chinchansure, Ashish A.; Arkile, Manisha A.; Shinde, Dinesh R.; Sarkar, Dhiman; Joshi, Swati P. (Planta Medica Letters, 2016)
The new 14,15-dinor-cis-labdane diterpene, named (+)-14,15-dinor-9α-hydroxy-cis-labd-11(E)-en-13-one (1), was isolated from the acetone extract of the aerial parts of Colebrookea oppositifolia, along with the known compounds alnustin (2), mosloflavone (3), flindulatin (4), 5,6,7-trimethoxy baicalein (5), tanetin (6), scutellarein 4′-methyl ether (7), apigenin (8), caffeic acid (9), anisofolin A (10), apigetrin (11), and forsythoside A (12). Structures of the new and known compounds were established by detailed analysis of 1D and 2D nuclear magnetic resonance studies. The isolated compounds 1–12 were evaluated for their antimycobacterium activity against Mycobacterium tuberculosis H37Ra and Mycobacterium bovis in both dormant and active phases. Compounds 1, 7, and 8 exhibited inhibitory activity against M. tuberculosis with IC50 values in the range of 8.1–55.0 µM (MIC 14.4–119.7 µM) in the active phase and 7.4–43.5 µM (MIC 11.5–123.3 µM) in the dormant phase. Similarly 1, 7, and 8 exhibited inhibitory activity against M. bovis with IC50 values in the range of 4.1–98.5 µM (MIC 13.7–161.0 µM) in the active phase and 4.1–111.1 µM (MIC 13.0–166.4 µM) in the dormant phase.